2001
DOI: 10.1021/jp003292z
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Nitrate, Hydroxyalkyl Nitrate, and Hydroxycarbonyl Formation from the NOx−Air Photooxidations of C5−C8 n-Alkanes

Abstract: Products of the gas-phase reactions of OH radicals with the n-alkanes n-pentane through n-octane at 298 ( 2 K and atmospheric pressure of air have been investigated using gas chromatography with flame ionization detection (GC-FID), combined gas chromatography-mass spectrometry (GC-MS), and in situ atmospheric pressure ionization tandem mass spectrometry. The formation yields of alkyl nitrates from n-hexane, n-heptane, and n-octane were measured by GC-FID, with the sum of the isomeric alkyl nitrates being 0.141… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
352
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(396 citation statements)
references
References 30 publications
39
352
4
1
Order By: Relevance
“…A source sample collected downwind of a working oil well with an oil storage tank showed elevated levels of CH 4 and C 2 -C 7 alkanes ( Table 2). The composition of hydrocarbons in this sample was similar to the composition of ''associated gas'' (i.e., found in conjunction with crude oil) (10,11). ''Nonassociated gas'' typically contains a higher percentage of methane and lower percentages of heavier alkanes (10).…”
Section: Discussionsupporting
confidence: 63%
“…A source sample collected downwind of a working oil well with an oil storage tank showed elevated levels of CH 4 and C 2 -C 7 alkanes ( Table 2). The composition of hydrocarbons in this sample was similar to the composition of ''associated gas'' (i.e., found in conjunction with crude oil) (10,11). ''Nonassociated gas'' typically contains a higher percentage of methane and lower percentages of heavier alkanes (10).…”
Section: Discussionsupporting
confidence: 63%
“…The plateau value of 0.202 for OH addition-normalized yields of β-HN formed from 2-methyl-1-alkene reactions is higher than the value of 0.162 measured for reactions of linear 1-alkenes, but lower than the value of ≈0.3 expected for secondary alkyl nitrates formed from reactions of n alkanes (11,16). The lower yields of β-HN are due to weakening of the O-O bond in the β-hydroxyperoxy radical-NO complex, RO-O-NO, by hydrogen bonding between hydroxy and peroxy groups (9).…”
Section: Resultsmentioning
confidence: 56%
“…AN, 1,4HN, and 1,4HC have been measured in the gas-phase for reactions of C 7 -C 10 alkanes, with yields of approximately 0.2, 0.05, and 0.5 (Reisen et al 2005) and with no other observed products. AN and 1,4HN yields are probably closer to ∼0.3 (Arey et al 2001) and ∼0.15 (Lim and Ziemann 2005) for reactions of larger alkanes. 1,4HC partition to particles and chamber walls where they isomerize to cyclic hemiacetals (CHA) [7] (note that the structure of the cyclic hemiacetal is that of an alkyl substituted 2-hydroxytetrahydrofuran).…”
Section: Reaction Mechanismmentioning
confidence: 69%
“…Reaction with O 2 forms a carbonyl [2] and decomposition creates two carbonyl [3, 4] plus alkyl radical pairs, with the alkyl radicals then reacting as described above. For linear alkanes with C n > 6, reactions with O 2 and decomposition are too slow to compete with isomerization (Arey et al 2001;Atkinson 2007), so carbonyl formation is negligible. Isomerization through a six-membered ring followed by reaction with O 2 forms 1,4-hydroxyperoxy radicals that react with NO similarly to alkylperoxy radicals.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation